2011
DOI: 10.1093/ije/dyr008
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in participation in an organized national colorectal cancer screening programme: results from the first 2.6 million invitations in England

Abstract: Overall uptake rates in this organized screening programme were encouraging, but nonetheless there was low uptake in the most ethnically diverse areas and a striking gradient by SES. Action to promote equality of uptake is needed to avoid widening inequalities in cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
269
4
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 267 publications
(307 citation statements)
references
References 26 publications
32
269
4
2
Order By: Relevance
“…A recent study using ELSA data, but including a broader age range, found a 57% uptake of screening (Gale, Deary, Wardle, Zaninotto, & Batty, 2015). Consistent with a previous study (von Wagner, Baio, et al, 2011), we found a strong gradient in uptake with 41.7% of individuals in the poorest and 65.5% in the richest quintiles of predicted nonpension wealth participating in screening. Our findings are also consistent with international studies showing the existence of a gradient in CRC screening regardless of broader system factors (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…A recent study using ELSA data, but including a broader age range, found a 57% uptake of screening (Gale, Deary, Wardle, Zaninotto, & Batty, 2015). Consistent with a previous study (von Wagner, Baio, et al, 2011), we found a strong gradient in uptake with 41.7% of individuals in the poorest and 65.5% in the richest quintiles of predicted nonpension wealth participating in screening. Our findings are also consistent with international studies showing the existence of a gradient in CRC screening regardless of broader system factors (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Uptake of screening was higher in our sample (61.0%) than in other studies (von Wagner, Baio, et al, 2011), probably because the age profile meant that the older participants were likely to have been invited over two or more rounds which, as reported recently, can increase uptake (Lo et al, 2014). A recent study using ELSA data, but including a broader age range, found a 57% uptake of screening (Gale, Deary, Wardle, Zaninotto, & Batty, 2015).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations